Development of flexible pavement design tool based on Jabatan Kerja Raya (JKR)’s revised guideline/ Mohamad Irwan P. Harahap - Harahap, Mohamad Irwan P.; Md Zin, Nurul Ain (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Land and road transport system provides a vital artery of communication, commerce and trade that helps to propel Malaysia towards national rapid growth, modernization and prosperity. In order to ensure standardization and compliance to the sanctioned road construction practice in the country, the Arahan Teknik (Jalan) 5/85 had been introduced and used extensively by the engineering community since 1985 for most of the road pavement design needs. However, over the years the guideline was incompatible with the technological advancement in the area, and consequently it suffers from design inadequacy and inflexibility, and lack of functionality and safety. Since 2013 however, Jabatan Kerja Raya Malaysia (JKR) has introduced the new Arahan Teknik (Jalan) 5/85 (Pindaan 2013) that is technically con-current and relevant to prevailing circumstances through incorporation of state-of-the-art technological developments in road pavement construction from across the world while addressing many a shortcoming of the former guideline. As in many an application in the industry as well as academia, migration to a new thinking or work process would be greatly facilitated and expedited with the aid of ICT tools. Excel VBA (Visual Basic for Application) provides such a familiar, common and convenient platform to develop the occasionally intensive and quite engaging computational processes but with the look and feel of commercial software and at a fraction of the cost, and practically reutilizing existing resources. Such development was addressed in this paper and used to solve a real world project, the results of which were in agreement with manual computations. Furthermore, the functionality and flexibility of the program would allow for multiple scenario investigation and comparison that would facilitate optimized design solution